The Effect of Professional Commitment, Organizational Communication and Knowledge Sharing on Teacher Performance with Teacher Work Satisfaction as Mediation at Private Vocational Schools in Bulakamba District, Brebes Regency - Diah Purwatiningrum; Gunistiyo; Mahben Jalil; Aminul Fajri (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
The purpose of this study was to analyze the effect of professional commitment on teacher performance, the effect of organizational communication on teacher performance, the effect of knowledge sharing on teacher performance, the effect of professional commitment on teacher job satisfaction, the effect of organizational communication on teacher job satisfaction, the effect of knowledge sharing on teacher job satisfaction, the effect of teacher job satisfaction on teacher performance, the effect of professional commitment on teacher performance with teacher job satisfaction as a mediator, the influence of organizational communication on teacher performance with teacher job satisfaction as a mediator, the effect of knowledge sharing on teacher performance with teacher job satisfaction as a mediator.The subjects of this study were all teachers at private vocational schools in Bulakamba District, Kab. Brebes with a total of 177 teachers. The data collection method used in this study is the questionnaire method. The research data analysis method is to test the validity and reliability of the instrument, descriptive statistics, quantitative analysis.